literasi keuangan pengaruh literasi keuangan terhadap perilaku keuangan mahasiswa universitas cokroaminoto palopo: pengaruh literasi keuangan terhadap perilaku keuangan mahasiswa universitas cokroaminoto palopo - naifasaputri; Artika sari devi; Haedar Haedar (Universitas Slamet Riyadi, 2024)
General knowledge of financial literacy has become an important part of daily life and is a life skill that must be possessed by every individual to live a long-term life based on SNLKI 2017, people who have knowledge and confidence in financial institutions, financial products and services, as well as the skills to know financial products and services are referred to as people who have a high level of literacy. This study aims to determine the effect of financial literacy on the financial behavior of Cokroaminoto Palopo University students. The research method used is quantitative with the data used is primary data. Data collection techniques using questionnaires. The sampling technique uses Random Sampling, where students have the same opportunity to be selected. The number of samples in this study was 30 respondents. The results of this study showed that partially the financial literacy variable (X) did not have a significant effect on the financial behavior variable (Y) of Cokroaminoto Palopo University students who were intended with a significant value of t test of 0.175. The results of this study are expected to provide information as a basis for understanding, studying, supporting and increasing reflection on the influence of financial literacy on financial behavior. The limitations of this study are: articles used only from Google Scholar so that search results cannot describe financial knowledge comprehensively, the research sample is lacking, and this study uses variables of financial literacy (X) and financial behavior (Y).